Hur kan man få ned dödligheten hos kalvarna i dikobesättningarna? - Höglund, Jenny (SLU/Rural Buildings and Animal Husbandry (until 121231), 2010)
This work is a literature review along with interviews from nine suckler herds. How to reduce calf mortality in the cow herd is the focus of this paper. To get profitability of a herd, it is important that you get a live calf per cow and year. Good fertility of the cows thus is very important. During the years 2007 - 2008, approximately 5.5% of all calves born by beef cows died and about 8.5% of the calves born by heifers died. Most calves die during calving. There are some statistics that show calf mortality has increased in recent years. It is important to find out why this is happening. The literature review was focused on feeding, body condition, rearing and breeding of the suckler cows and heifers and how it may affect the mortality of the calves. An important factor that should be kept in mind is the body condition of the cow. A fat cow can have more calving difficulties than a cow in normal body condition. A thin and malnourished cow is likely to have a weak calf which may have difficulties to survive. It is important to make assessments of the body condition of the cows and heifers during the year in order for the feeding strategy. A proper feeding plan is essential in order to avoid drastic changes in the body condition during the final weeks of pregnancy. The strategy should also include feeding of cows which are thin at weaning. Restricted feeding results in competition for feed which leads to that some cows consume too much feed and some too little. Therefore, it is important to be able to group the animals according to nutritional needs. Heifers and cows in poor body condition needs to have the opportunity to feed according to their needs. The cows could be fed high-quality silage, but it is also important that they do not get too much of this as the have a risk of overfeeding. The ration should therefore be balanced with straw. Free access to minerals and a salt lick is also important for the animals. There are a number of factors in breeding to consider for reducing mortality. These are: the birth weight, calving difficulties and stillborn calves. Inheritance for stillborn calves is low and therefore difficult to select for. Therefore the focus should be on easy calving and calf birth weight in order to reduce calf mortality. It is very important to consider calving characteristics when choosing the breeding cow in the herd. A cow with difficult calving or a heifer with a parent with severe calving should not be recruited to the herd. Housing systems during winter for the cows in Sweden range from tied system to loose housing systems and out door ranching. During calving it is important that the cow and calf go together for a while, if needed in order to bond. If the calving takes place during the cold season, farmers should have a warm room for the calf available in the event of complications. The compilation of the interviews with the farmers shows that there are a number of elements in the production that we can pursue in order to reduce mortality. In all herds, there was no major difference of the feeding of the animals within each herd. By grouping animals according to body condition and age it will facilitate to meet their nutritional requirements. Assessment of body condition of the animals was not very regular at the farms even though it is a simple method. It is also an important factor for the cow to have the right body condition at calving. On the visited farms, many cows were in optimal body condition. The farmers generally had few problems with calving difficulties and they hade few still born calves. It is important that the farmers target appropriate birth weights of calves. A heifer should not be covered with a bull which gives high birth weight of calves. Cows that give stillborn calves should be removed. Heifers should not be recruited from dams which have a history of calving difficulties. Finally, heifers should be assessed for their size / weight before being covered so that the heifer is at an optimal size when she is having her first calf.